THE USE OF JEOPARDY STRATEGY TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT THE SEVENTH GRADE STUDENTS OF SMPN 26 MAKASSAR - Haris, Fitri Rahmayanti; Asriati, St; Maruf, Amar (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2018)
The objective of this research was to find out the improvement of the students’ vocabulary mastery through the use of Jeopardy Strategy at the seven grade students of SMPN 26 Makassar 2017/2018. The research applied quasi-experimental design with two groups’ pre-test and post-test design. The population of this research was the students of SMPN 26 Makassar 2017/2018 which consisted of 364 students of 9 class. The sample was taken by using purposive sampling technique which consisted of two groups. The researcher took the thirty-seven students as experimental class and the thirty-six students as control class. The instrument of this research was a multiple choice, matching words and fill the blank test used in pre-test and post-test. The result of the data indicated that there was a significant difference between students’ post-test in experimental class and controlled class.  The mean score of post-test (70, 11) in experimental class was greater than the mean score of post-test (64, 11) in controlled class. From t-test, the researcher found that the value of t-test (3,172) was greater than t-table (1,994) at the level of significance 0.05 with degree of freedom (df) = 71. Finally the improvement of the students’ vocabulary mastery by using Jeopardy Strategy was improve significantly.